Mesenchymal Stem Cells in Renal Fibrosis: The Flame of Cytotherapy - Quan Zhuang; Ruoyu Ma; Yanshuang Yin; Tianhao Lan; Meng Yu; Yingzi Ming (Stem Cells International)
Renal fibrosis, as the fundamental pathological process of chronic kidney disease (CKD), is a pathologic extension of the normal wound healing process characterized by endothelium injury, myofibroblast activation, macrophage migration, inflammatory signaling stimulation, matrix deposition, and remodelling. Yet, the current method of treating renal fibrosis is fairly limited, including angiotensin-converting enzyme inhibition, angiotensin receptor blockade, optimal blood pressure control, and sodium bicarbonate for metabolic acidosis. MSCs are pluripotent adult stem cells that can differentiate into various types of tissue lineages, such as the cartilage (chondrocytes), bone (osteoblasts), fat (adipocytes), and muscle (myocytes). Because of their many advantages like ubiquitous sources, convenient procurement and collection, low immunogenicity, and low adverse effects, with their special identification markers, mesenchymal stem MSC-based therapy is getting more and more attention. Based on the mechanism of renal fibrosis, MSCs mostly participate throughout the renal fibrotic process. According to the latest and overall literature reviews, we aim to elucidate the antifibrotic mechanisms and effects of diverse sources of MSCs on renal fibrosis, assess their efficacy and safety in preliminarily clinical application, answer the controversial questions, and provide novel ideas into the MSC cellular therapy of renal fibrosis.